Comparative analysis of pediatric SHH medulloblastoma DAOY spheres and adherent monolayers: implications for medulloblastoma research - Jana Klementová; Šárka Jarošová; Irina Danilová; Markéta Farníková; Josef Novotný; Marie Davídková; Martina Zíková (Cancer Cell International)
Abstract Medulloblastoma, the most prevalent brain tumor among children, requires a comprehensive understanding of its cellular characteristics for effective research and treatment. In this study, we focused on DAOY, a permanent cell line of medulloblastoma, and investigated the unique properties of DAOY cells when cultured as floating multicellular aggregates called spheres, as opposed to adherent monolayers. Through our comprehensive analysis, we identified distinct characteristics associated with DAOY spheres. Our findings demonstrate that DAOY spheres express markers for both neural stem cells, such as CD133 (PROM1), and differentiated neurons, exemplified by MAP2. Additionally, our investigation revealed that spheres-derived cells exhibit heightened resistance to ionizing radiation compared to adherent cells. Consequently, our results indicate that caution is advised when interpreting experimental results obtained from adherent cell cultures and extrapolating them to in vivo situations.